The Optimal Consumption of Depletable Natural Resources: An Elaboration, Correction, and Extension - Cropper, M. L.; Weinstein, Milton C.; Zeckhauser, Richard J. (Quarterly Journal of Economics, 1978)
I. Optimality of competitive markets with increasing marginal extraction costs—a correction and elaboration, 338.—II. Cases where extraction rights or extraction technologies must be traded, 341.—III. Conclusion, 343.